Hematological profile of untreated or ionizing radiation-exposed cyclooxygenase-2-deficient mice - Hofer, M; Hoferová, Z; Dušek, L; Souček, K; Gruzdev, A (Physiological research, 2017)
We investigated hematopoiesis in untreated and ionizing radiation-exposed cyclooxygenase-2-deficient (COX-2 KO) mice. We performed a complex hematological analysis of 16 parameters in untreated COX-2 KO male mice or COX-2 KO male mice irradiated with the dose of 4 Gy of gamma-rays and their wildtype littermates. At baseline, hematopoiesis was increased in COX-2-deficient mice, but attenuated by irradation in COX-2-deficient mice compared to wildtype. To conclude, the anti-inflammatory action of the COX-2 genetic disruption plays a positive role in hematopoiesis under basal conditions but is detrimental following radiation exposure.
Keywords: ionizující záření; Animals; hematopoéza; Hematopoiesis; myši knockoutované; mužské pohlaví; zvířata; Mice; Male; Mice, 129 Strain; cyklooxygenasa 2; Radiation, Ionizing; myši kmene 129; Cyclooxygenase 2; Mice, Knockout; myši